Effects of heat stress on endocrine, thermoregulatory, and lactation capacity in heat-tolerant and -sensitive dry cows - Chen, Xiaoyang; Li, Chenyang; Fang, Tingting; Yao, Junhu; Gu, Xianhong (Frontiers in Veterinary Science, 2024)
Increasing global temperatures present a significant challenge to livestock production. The dry period is an important stage in the production cycle of cow, and environmental heat stress (HS) during this period can have adverse effects on the subsequent lactation performance. In this study, we aimed to investigate the effects of HS on endocrine, thermoregulatory, and lactation parameters in heattolerant dry cows (HTDC) and heat-sensitive dry cows (HSDC). We measured the respiratory rate (RR), body temperature (BT), and temperature-humidity index (THI) in 66 dry cows during HS. The slopes of RR and BT to THI were determined through analysis of measurements and dry cows background information using a mixed-effects model. Subsequently, the heat tolerance or sensitivity of dry cows was assessed using clustering method (HTDC = 19 and HSDC = 47). Compared with that of HSDC, the RR of HTDC significantly increased after exposure to HS (P < 0.05). The average reduction in milk yield from new lactation to the previous lactation was significantly lower in HTDC compared to HSDC (P < 0.05). Plasma cortisol and non-esterified fatty acid levels were significantly lower in HTDC compared to HSDC (P < 0.05), while plasma triiodothyronine (P = 0.07) and growth hormone (P = 0.08) levels tended to be higher in HTDC relative to HSDC. HTDC can more effectively alleviate the impacts of HS through their superior thermoregulation and metabolism, thereby ensuring optimal postpartum lactation performance.